Supposedly identical microplastic particles substantially differ in their material properties influencing particle-cell interactions and cellular responses - Ramsperger, A. F. R. M.; Jasinski, J.; Volkl, M.; Witzmann, T.; Meinhart, Marcel; Jerome; Kretschmer, W. P.; Freitag, R.; Senker, J.; Fery, Andreas; Kress, H.; Scheibel, Thomas; et al. (Journal of Hazardous Materials, 2022)
Microplastics and its putative adverse effects on environmental and human health increasingly gain scientific and public attention. Systematic studies on the effects of microplastics are currently hampered by using rather poorly characterised particles, leading to contradictory results for the same particle type. Here, surface properties and chemical composition of two commercially available nominally identical polystyrene microparticles, frequently used in effect studies, were characterised. We show distinct differences in monomer content, ζ-potentials and surface charge densities. Cells exposed to particles showing a lower ζ-potential and a higher monomer content displayed a higher number of particle-cell-interactions and consequently a decrease in cell metabolism and proliferation, especially at higher particle concentrations. Our study emphasises that no general statements can be made about the effects of microplastics, not even for the same polymer type in the same size class, unless the physicochemical properties are well characterised.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Cellular internalisation; CP-AFM; Cytotoxicity; EDX; GPC; Material properties; Microplastic; NMR; ζ-potential